2015
DOI: 10.3402/fnr.v59.28916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MW-assisted roasting on nutritional and chemical properties of hazelnuts

Abstract: In order to enhance the flavor, texture, color, and appearance of hazelnuts, they are roasted during postharvest processing. In this study, raw hazelnuts (Corylus avellana L.) were roasted using microwave (MW) and MW-assisted hot air methods under various roasting conditions. The hazelnuts roasted were then examined to determine the percent DPPH radical scavenging activity, antioxidant capacity, total phenolic content, resistant starch, non-resistant starch, total starch, and protein concentration. The roastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…With the increase in the roasting temperature, there was a decrease in h* values in both cultivation methods (P˂0.05). Kalkan et al (2016) reported a similar result. Malekjani et al (2017) showed that the h value decreased with the increase in the roasting temperature and duration.…”
Section: Colorimetric Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…With the increase in the roasting temperature, there was a decrease in h* values in both cultivation methods (P˂0.05). Kalkan et al (2016) reported a similar result. Malekjani et al (2017) showed that the h value decreased with the increase in the roasting temperature and duration.…”
Section: Colorimetric Analysissupporting
confidence: 58%
“…However, parallel to the increase in temperature, C* values of all samples were increased (P˂0.05). Chroma refers to color intensity (Kalkan et al, 2016). It was determined that hazelnuts had a more intense color with the increase in the roasting temperature.…”
Section: Colorimetric Analysismentioning
confidence: 99%
“…Mostly, no statistical differences in total antioxidant activity have been observed among samples of unroasted and roasted kernels without skins; the thermal processing had a light negative trend in antioxidant efficacy mainly due to the absence of skins [1,27,50,52,59]. The effects of kernel roasting by 2 different processing methods, microwave and microwave-assisted hot air, revealed in both cases an increase of antioxidant activity at the rising of roasting time and temperature was observed, maybe explainable according to the formation of new Maillard reaction products having antioxidant activity [56,60].…”
Section: Antioxidant Activitymentioning
confidence: 95%
“…An example of ellagitannin, in which at least 2 galloyl units are C-C coupled to each other, is represented by ellagic acid (56), found in the hazelnut kernel [23] (▶ Fig. 4).…”
Section: Tannins and Proanthocyanidinsmentioning
confidence: 99%
See 1 more Smart Citation